ADDIE-Based Google Sites Media Development: Feasibility and Effectiveness Test on Creativity, Innovation, and Entrepreneurship Learning in Vocational Schools - Mardani, Wina; Warneri; Ariyati, Eka; Salam, Urai; Halida (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2026)
Entrepreneurship is still not utilized optimally, which has an impact on the low achievement of student learning outcomes. This research aims to develop google sites-based learning media on business opportunity materials and test its feasibility and effectiveness. The method used is Research and Development (R&D) with the ADDIE model, which was carried out at the State Vocational School 1 Kuala Mandor B, Kubu Raya Regency, with 23 students in grade XI. The research instruments included expert validation sheets and multiple-choice questions. Data analysis was carried out through the calculation of eligibility percentage, normality test, paired sample t-test, and N-Gain. The results showed that the media was in the very feasible category with an assessment percentage of 88.21% from media experts and 88.89% from material experts. There was a significant increase in learning outcomes (Sig. 0.000 < 0.05) with the average score increasing from 55.87 to 86.09. The N-Gain value of 0.7112 was in the high category, which indicates that the media is effective in improving student learning outcomes. Theoretically, this study supports the application of the ADDIE model in the development of google sites-based media. Practically, media can be used as an interactive learning alternative to improve the quality of learning in vocational education.